The Use of 16S Ribosomal RNA PCR to Investigate Donor Derived Transport Fluid Infections in Patients Undergoing Renal Transplantation: A Retrosepctive Audit of 36 Deceased Donors. (July 2018) - Shanmuganathan, Prashant; O'doherty, Jonathan; Fares, Rami; Black, John; Yates, James; Doughman, Tahir; Rizzello, Anna; Bukhari, Sayed; Bagul, Atul
Abstract : Introduction: 16S ribosomal RNA (rRNA) gene polymerase chair reaction (PCR) is emerging as a high yield molecular method for the detection and identification of bacterial pathogens in clinical specimens with a high suspicion for infection. This is advantageous in the detection of pathogens which may have gone undetected in routine laboratory cultures. Methods: Transport fluid obtained from 36 deceased donors was assessed by two different methods. The fluid was sent for bacterial culture, which is the current gold standard, and in addition further assessment via 16S PCR was performed for comparison. Results: The average donor age was 46.7 years. 58.3% were DBD donors. 38% of donors were being treated for infection. 52% of all donors received a dose or course of antibiotics within 72 hours prior to retrieval. 48% of donors grew a bacterial pathogen on standard bacterial culture; however 7% were thought to be secondary to contamination. 16S RNA PCR was performed on 62% of fluid samples where a positive standard bacterial culture was obtained. 16S PCR detected 21% of bacterial pathogens in samples with a positive standard culture. Discussion: We identified two issues to address, 1. 16S PCR was not consistently performed on all fluid samples which had a positive laboratory culture 2. the 16S PCR bacterial detection rate in the cohort with a positive culture was comparitively low. In some instances it was not possible to identify organisms to species level due to the presence of multiple species and variants of microorganism. There is a need to standardise the 16S PCR technique on transport fluids by addressing the presence of potential inhibitors in these samples and by improving the design of primers. Conclusion: There is limited understanding of the use of 16S PCR for detection of infection in cadaveric donors. 16S PCR has the potential to improve yield of pathogens and help tailor antibiotic therapy of the patient in line with antimicrobial stewardship. However, there is a need to standardise the technique for optimal results in solid organ donor derived infections.